A thioacidolysis method tailored for higher‐throughput quantitative analysis of lignin monomers. Issue 10 (14th September 2016) - Harman‐Ware, Anne E.; Foster, Cliff; Happs, Renee M.; Doeppke, Crissa; Meunier, Kristoffer; Gehan, Jackson; Yue, Fengxia; Lu, Fachuang; Davis, Mark F.
Abstract: Thioacidolysis is a method used to measure the relative content of lignin monomers bound by β‐O‐4 linkages. Current thioacidolysis methods are low‐throughput as they require tedious steps for reaction product concentration prior to analysis using standard GC methods. A quantitative thioacidolysis method that is accessible with general laboratory equipment and uses a non‐chlorinated organic solvent and is tailored for higher‐throughput analysis is reported. The method utilizes lignin arylglycerol monomer standards for calibration, requires 1–2 mg of biomass per assay and has been quantified using fast‐GC techniques including a Low Thermal Mass Modular Accelerated Column Heater (LTM MACH). Cumbersome steps, including standard purification, sample concentrating and drying have been eliminated to help aid in consecutive day‐to‐day analyses needed to sustain a high sample throughput for large screening experiments without the loss of quantitation accuracy. The method reported in this manuscript has been quantitatively validated against a commonly used thioacidolysis method and across two different research sites with three common biomass varieties to represent hardwoods, softwoods, and grasses. Abstract : Thioacidolysis converts arylglycerol lignin monomers, particularly those bound by β‐O‐4 linkages, to corresponding thioethyl monomers. A high‐throughput and quantitative thioacidolysis method was developed and validated across laboratories and compared to the results of other thioacidolysis methods. The high‐throughput method uses aryglycerol standards for quantitation, does not require product concentration steps and can utilize rapid GC methods for analysis.